Narasi Radikalisme-Terorisme di Website Tahun 2022: Upaya Menumbuhkan Pemahaman Moderat - Gazali, Hatim; Khoirul Anwar, Muhammad; Mubarok, Syahril (Mozaic : Islam Nusantara, 2024)
This study aims to analyze the radicalism-terrorism narrative on online media websites in 2022 as an effort to foster moderate understanding in accessing digital media. This research method was carried out using netnography. The results of research on indicators of radicalism found evidence that it was still high. Some of the narratives that were developed became the tendency of each media. This means that not all Islamic media are massively framing the caliphate issue. This fact was found based on searching through keywords on each website that was the object of research. For example, in the media eramuslim.com, the percentage of narratives framing the issue of the caliphate is still low when compared to other narratives